2009
DOI: 10.1121/1.3224715
|View full text |Cite
|
Sign up to set email alerts
|

On the assimilation-discrimination relationship in American English adults’ French vowel learning

Abstract: A quantitative "cross-language assimilation overlap" method for testing predictions of the Perceptual Assimilation Model ͑PAM͒ was implemented to compare results of a discrimination experiment with the listeners' previously reported assimilation data. The experiment examined discrimination of Parisian French ͑PF͒ front rounded vowels /y/ and /oe/. Three groups of American English listeners differing in their French experience ͑no experience ͓NoExp͔, formal experience ͓ModExp͔, and extensive formal-plus-immersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 36 publications
10
50
0
Order By: Relevance
“…Holliday performance on L2 perception tasks (Flege et al, 1997;Ingram and Park, 1997;Levy, 2009b;Tees and Werker, 1984), suggesting that in some cases L1 influence on L2 speech perception can be overcome with sufficient L2 experience.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Holliday performance on L2 perception tasks (Flege et al, 1997;Ingram and Park, 1997;Levy, 2009b;Tees and Werker, 1984), suggesting that in some cases L1 influence on L2 speech perception can be overcome with sufficient L2 experience.…”
mentioning
confidence: 99%
“…When the results in Levy (2009b) were broken down by vowel context, it was found that the HiExp listeners were more accurate than the ModExp listeners in discriminating between /oe/ and /o/, but not between /y/ and /u/. Thus, even though the HiExp listeners had surely been exposed to many more exemplars of French /y/ and /u/ than the ModExp listeners, this increased experience did not lead to more accurate discrimination between the two vowel sounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…AE [i+, ae+, U, u+] were each consistently assimilated to only one of the five spectral categories, but categorization as one-or two-mora J vowels was inconsistent both within and across J listeners, and [ae+] was categorized as more similar to a palatalized vowel on a substantial number of trials. Using the group patterns of perceptual assimilation, the 13 contrasting pairs were categorized in terms of PAM patterns, and in terms of overlap scores (Levy, 2009 Table 2, along with the group results on the AXB discrimination test.…”
Section: Resultsmentioning
confidence: 99%
“…For each contrast and gender, the acoustic overlap score is the smaller percentage of classifications when two members of a BP contrast produced by the ES speakers were classified as the same BP vowel (cf. Levy, 2009). For example, the acoustic overlap score of /o-ɔ/ for male ES speakers is 50 %: 34 % of /o/ tokens and 3 % of /ɔ/ tokens were classified as /o/, whereas 47 % of /o/ tokens and 95 % of /ɔ/ tokens were classified as /ɔ/; summing the smaller percentages when both members were classified as the same BP vowel, i.e., 3 % + 47 %, gives 50 %.…”
Section: Relationship Between Non-native Production and Perceptionmentioning
confidence: 99%